Differences in arousal probability and duration after apnea and hypopnea events in adult obstructive sleep apnea patients. (5th November 2018) - Leppänen, Timo; Kulkas, Antti; Oksenberg, Arie; Duce, Brett; Mervaala, Esa; Töyräs, Juha
Abstract: Objective : In obstructive sleep apnea (OSA), breathing cessations are often followed by arousals, leading to sleep fragmentation and thus impaired sleep quality. Arousals and fragmented sleep are also related to detrimental cardiovascular events. The key index for OSA diagnosis (i.e. the apnea–hypopnea index) attributes equal diagnostic value to apneas and hypopneas, despite the fact that the associated arousals and desaturations may be very different. Thus, considering the severity of the consequences of apneas and hypopneas could enhance the estimation of OSA severity. In this study, we investigate whether the probability and duration of apnea- and hypopnea-related arousals differ and whether the differences in desaturation severity following apneas and hypopneas are dependent on sleep stage. Approach : Polysomnographic recordings of 348 consecutive OSA patients were included for analysis. The severity of arousals and desaturations associated with hypopneas within different sleep stages was compared to that of arousals and desaturations associated with apneas. In addition, the probability of arousals related to apneas and hypopneas was evaluated within OSA severity categories. Main results : Apneas caused arousals less frequently than hypopneas in N1, N2, and N3 sleep in all OSA severity categories. However, the arousals caused by apneas were longer ( p   <  0.001) and the desaturations related to apneas were more severe ( p   <  0.001) than those related to hypopneas in N1, N2, and rapid eye movement sleep even after adjustment for respiratory event durations. Significance : Desaturations and arousals related to apneas are more severe than those related to hypopneas. Therefore, apneas followed by arousal or desaturation should have a different diagnostic value than hypopneas when assessing OSA severity and related risk for cardiovascular consequences.